P20 First report of the long-term efficacy of a novel endoscopic radiofrequency ablation technique for malignant biliary obstruction. (6th September 2011) - Kallis, Y; Phillips, N; Steel, A; Baldwin, C; Nicholls, J; Jiao, L; Vlavianos, P; Habib, N; Westaby, D
Abstract : Introduction: Insertion of self-expanding metal stents (SEMS) is standard practice in patients with unresectable malignant biliary strictures. Stent occlusion is a significant clinical problem in patients surviving beyond 3 months. A pioneering phase I/II study in our tertiary referral centre demonstrated good safety and 30-day patency using a novel endoscopic radiofrequency ablation (RFA) technique as an adjunct to SEMS.1 The longer term impact of combined RFA+SEMS on biliary drainage and overall patient survival is unknown. Aim: To investigate long-term safety and efficacy of endobiliary RFA in malignant bile duct obstruction. Method: Retrospective cohort analysis of 24 patients undergoing RFA+SEMS (17 pancreatic carcinoma; 7 cholangiocarcinoma) and 44 matched controls undergoing SEMS insertion alone (34 pancreatic carcinoma, 10 cholangiocarcinoma) for malignant biliary obstruction in a single tertiary referral centre. Patients were matched for age, sex, disease, presence of metastases, ASA/co-morbidities, and intention to treat with palliative chemotherapy. Patients with a potential minimum of 6-month follow-up were included and survival, maintenance of stent patency and procedure-related complications were assessed. Results: RFA treated and control cohorts were closely matched- mean age 71.8±9.8 yrs vs 68.8±10.3, metastases at treatment 9/24 (38%) vs 17/44 (39%), chemotherapy 16/24 (67%) vs 27/44 (61%). Kaplan–Meier analysis showed a median survival of 227 days in the RFA group vs 159 days in controls (p=0.067). Multivariate analysis showed RFA treatment to be the strongest predictor of survival at 90 days (OR 26.1, p=0.011). Survival benefits may extend beyond 90 days (OR 2.8, p=0.071 at 180 days; OR 2.8, p=0.102 at 360 days), but require further investigation. Within 6 months after treatment, more patients were alive with a patent first SEMS in the RFA cohort than in controls. Complications of RFA were few (1 pancreatitis, 2 cholecystitis) and comparable to those associated with standard ERCP alone. The procedure was well-tolerated with a median post-procedure inpatient stay of 1 day (1–24). Conclusion: In the single largest case series studied to date, endobiliary RFA is a safe and efficacious treatment for malignant biliary obstruction, with potential early survival benefit. Large multi-centre prospective trials of this novel treatment modality are warranted.